18 Element Massive MIMO/Diversity 5G Smartphones Antenna Design for Sub-6 GHz LTE Bands 42/43 Applications - Naveen Jaglan (IEEE Open Journal of Antennas and Propagation, 2021)
This work presents an 18 element antenna system compatible with massive multiple input multiple output (MIMO)/Diversity fourth/fifth generation (4G/5G) smartphones. The antennas are designed at sub-6 GHz long term evolution (LTE) band 42 (3.4-3.6 GHz) and LTE band 43 (3.6-3.8 GHz). A simple slot type antenna is considered as the radiating element, with open ended slots used for obtaining a compact design. These slots also act as decoupling elements to improve the isolation among different radiators. The proposed antenna elements are designed on a low-cost FR-4 substrate having dimension of 150 mm $×80$ mm $×1.6$ mm, which can be typically used for 6-inch smart phones. The simulated and measured values of antenna gain are found to be greater than 5.3 dBi. Simulated and measured results of the proposed design show excellent impedance matching (reflection coefficient>20 dB), port isolation (>20 dB), total efficiency (>87%) and Envelope Correlation Coefficient (< 0.01) over the operating frequency. MIMO antenna performance metrics are verified by calculating the ergodic channel capacity with Kronecker channel model.